2007
DOI: 10.1097/jcp.0b013e31815abf0e
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Single-Dose Sertraline on the Hypothalamus-Pituitary-Adrenal System, Autonomic Nervous System, and Platelet Function

Abstract: Initiating sertraline treatment increases HPA system activity and epinephrine concentrations. We found no clinically relevant effect of single-dose sertraline treatment on autonomous nervous function, platelet activity, or platelet 5-HT uptake. These findings may not be extrapolated to patients with affective or cardiac disorders or to other SSRIs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
1

Year Published

2008
2008
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 39 publications
1
13
0
1
Order By: Relevance
“…However, previous studies reported conflicting results, and time after initiation of treatment and the clinical state seem to be important variables. Some studies reported increased HRV variability during SSRI treatment (50 -52) whereas others found no difference or a reduction (1,(53)(54)(55). Here, we included a large set of autonomic parameters to allow more detailed insights into autonomic function.…”
Section: Discussionmentioning
confidence: 97%
“…However, previous studies reported conflicting results, and time after initiation of treatment and the clinical state seem to be important variables. Some studies reported increased HRV variability during SSRI treatment (50 -52) whereas others found no difference or a reduction (1,(53)(54)(55). Here, we included a large set of autonomic parameters to allow more detailed insights into autonomic function.…”
Section: Discussionmentioning
confidence: 97%
“…The effect of selective serotonin reuptake inhibitor anti- depressants (SSRIs) on HRV was much less clear. Some studies reported increased HRV during SSRI treatment (28,39,53), whereas others found no difference or a reduction (1,12,37). SNRIs were reported to reduce HRV in most of studies (41,54,56).…”
Section: Discussionmentioning
confidence: 99%
“…Ahrens and colleagues [62] found no effect of a single dose sertraline treatment on HRV in healthy young adults. In Heart Fail Rev (2009) 14:35-50 37 contrast, Glassman and colleagues [63] observed decreased HRV in depressed patients treated with sertraline vs. placebo following acute coronary syndrome.…”
Section: Autonomic Nervous System Function and Treatment Of Depressionmentioning
confidence: 97%